2014
DOI: 10.1080/11035897.2013.866978
|View full text |Cite
|
Sign up to set email alerts
|

Depositional framework of the East Baltic Tremadocian black shale revisited

Abstract: This article presents a centimetre-to micrometre-scale study of sedimentary fabrics from Lower Ordovician metalliferous black shale from the Baltic palaeobasin. Two sections of the Türisalu Fm. NW and NE Estonia were analysed with light microscopy and scanning electron microscopy. This rock unit is characterised by mostly thin bedding (,10 mm), common occurrence of minor erosional features, and a large variety of sedimentary fabrics, including graded, cross-laminated and massive fabrics. Based on this, we sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 76 publications
0
19
0
Order By: Relevance
“…The cyclicity of V abundance might be linked to factors such as alteration of thermohaline circulation or water depth fluctuations and related cyclic changes in dissolved oxygen availability near the sea bottom. On the other hand, Hints et al (2014) suggested that high primary productivity rates driven by phosphate loading and effective recycling in the shallow water column (sea bottom within the photic zone) characterized the accumulation of the muds of the Türisalu Fm. The recorded V pattern might thus be connected to cyclic changes in nutrient loading and palaeoproductivity.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…The cyclicity of V abundance might be linked to factors such as alteration of thermohaline circulation or water depth fluctuations and related cyclic changes in dissolved oxygen availability near the sea bottom. On the other hand, Hints et al (2014) suggested that high primary productivity rates driven by phosphate loading and effective recycling in the shallow water column (sea bottom within the photic zone) characterized the accumulation of the muds of the Türisalu Fm. The recorded V pattern might thus be connected to cyclic changes in nutrient loading and palaeoproductivity.…”
Section: Discussionmentioning
confidence: 98%
“…Based on the biostratigraphic framework and a recent time scale calibration (Cooper & Sadler 2012), one could argue that the primary muds of the Türisalu Fm. should have been deposited within a maximum time frame of ~ 5 My (Hints et al 2014). Whereas the long-term accumulation rates apparently stayed very low during sedimentation of the primary organic-rich muds of the Türisalu Fm., the sedimentary fabrics in the black shales suggest dynamic deposition, frequent reworking of sea bottom and changes in deposition rates (Hints et al 2014).…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations